Modelagem geológica e projeção de avanço de lavra a partir da comparação de diferentes métodos de cálculo de PN para uma mina de calcário dolomítico, em Caçapava do Sul – RS - (:unkn) unknown (Universidade Federal do Pampa, 2025)
The extraction of dolomitic limestone plays a fundamental role in the economic development of Caçapava do Sul, RS, particularly due to the production of highquality agricultural lime. However, as it is a product with low added value, it is essential to develop methods that optimize the use of the mineral deposit and ensure the quality of the final product. In this context, this study aimed to evaluate the impact of different methods of obtaining and calculating the Neutralization Power (PN) on deposit evaluation and on the pushback planning of a local mine. For this purpose, data from rotary-percussion drilling, laboratory analyses, and aerophotogrammetric surveying were integrated to generate three-dimensional models of the ore body. PN was determined through the titrimetric method, and the acidic PN by means of complexometric analyses with EDTA. CaO and MgO grades were also determined by the EDTA complexometric method and were used to calculate two derived forms of PN: the calculated PN (pre-estimation) and PN (CaO+MgO) (post-estimation). Block models were estimated using the Inverse Distance Squared (ID²) method and validated statistically. The results showed that differences among the methods and calculation approaches for PN were small, with variations of less than 1% in mean values and good preservation of statistical and spatial patterns. The explicit geological modeling generated a solid consistent with the geometry observed in the drilling data, allowing the development of coherent block models. The pushback projections resulted in waste-to-ore ratios (WOR) ranging from 0.329 to 0.331 m³/t, indicating that the choice of method or form for calculating PN does not significantly alter the estimation of values in unsampled locations. Additionally, areas with PN greater than 100% were identified, especially south of the southern pit, highlighting zones with potential for lime production and increasing product value.
Keywords: Mineração; Modelagem geológica; Avanço de lavra; Mining; Geological modeling; Pushback; CIENCIAS EXATAS E DA TERRA